2016
DOI: 10.1016/j.ejbas.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and extracellular enzyme activities of fungal endophytes isolated from medicinal plants of Western Ghats, Karnataka

Abstract: A total of 112 endophytic fungi belonging to 26 genera were isolated from six wild medicinal plants belonging to Bisle region, Western Ghats of Karnataka, among which Hedychium flavescens Carey ex Roscoe and Hedychium coronarium J. Koenig are listed as endangered plants in the Red data book. The endophytic fungal diversity and extracellular enzyme activity from the endangered plants are reported for the first time. The diversity of the fungal isolates was analyzed using Simpson's diversity indices, Shannon-Wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 16 publications
6
19
0
Order By: Relevance
“…The leaves showed the second highest H' index value (1.79), and have the same level of diversity index (medium level) as reported in other study (H'=1.97) (Gupta dan Chaturvedi 2017). Similar results were also reported on the endophytic fungi isolated from Piper nigrum in which the root had higher H' value (H'=1.33) than leaf (H'=0.69) and petiole (H'=0.69) (Uzma et al 2016).…”
Section: Diversity Indexsupporting
confidence: 86%
“…The leaves showed the second highest H' index value (1.79), and have the same level of diversity index (medium level) as reported in other study (H'=1.97) (Gupta dan Chaturvedi 2017). Similar results were also reported on the endophytic fungi isolated from Piper nigrum in which the root had higher H' value (H'=1.33) than leaf (H'=0.69) and petiole (H'=0.69) (Uzma et al 2016).…”
Section: Diversity Indexsupporting
confidence: 86%
“…The present study results showed that Aspergillus genus was the most common isolate followed by Eladia "Penicillium related strains (7)" and Cladosporium. Aspergillus, Penicillium, and Cladosporium were also reported among the dominant endophytic isolates obtained in many other studies (15)(16)(17).…”
Section: Resultssupporting
confidence: 58%
“…In contrast, many true phytopathogenic fungi have developed mechanisms to actively cross barriers to the outer structure of plants, cuticles and cell walls of the epidermis. Fungi generally secrete a number of hydrolysis enzymes, including cutaneous, cellulase, pectinase and protease (Uzma et al, 2016).…”
Section: Treatment Combination Of Pathogenic Fungi and Weedsmentioning
confidence: 99%